Transforming the accounting profession through Thuthuka : an outcome-based evaluation of the Thuthuka Bursary Fund programme as implemented at Stellenbosch University - Frans, Ilse (Stellenbosch : Stellenbosch University, 2022)
Thesis (MPA)--Stellenbosch University, 2022.